Genome-wide association meta-analysis of corneal curvature identifies novel loci and shared genetic influences across axial length and refractive error - Qiao Fan; Alfred Pozarickij; Nicholas Y Q Tan; Xiaobo Guo; Virginie J M Verhoeven; Veronique Vitart; Jeremy A Guggenheim; Masahiro Miyake; J Willem L Tideman; Anthony P Khawaja; Liang Zhang; Stuart MacGregor; et al. (Springer Nature, 2022)
Corneal curvature, a highly heritable trait, is a key clinical endophenotype for myopia - a major cause of visual impairment and blindness in the world. Here we present a trans-ethnic meta-analysis of corneal curvature GWAS in 44,042 individuals of Caucasian and Asian with replication in 88,218 UK Biobank data. We identified 47 loci (of which 26 are novel), with population-specific signals as well as shared signals across ethnicities. Some identified variants showed precise scaling in corneal curvature and eye elongation (i.e. axial length) to maintain eyes in emmetropia (i.e. HDAC11/FBLN2 rs2630445, RBP3 rs11204213); others exhibited association with myopia with little pleiotropic effects on eye elongation. Implicated genes are involved in extracellular matrix organization, developmental process for body and eye, connective tissue cartilage and glycosylation protein activities. Our study provides insights into population-specific novel genes for corneal curvature, and their pleiotropic effect in regulating eye size or conferring susceptibility to myopia.